Relationship between stride length and 80 meter sprint run of fifth grade students at Meok State Elementary School, North Bengkulu - Haryodi, Monas; Perdima, Feby Elra; Sumantri, Ajis (Journal of Physical Education and Sports, 2024)
This study aims to determine the relationship between stride length and 80 Meter sprint running skills of fifth grade students of SD Negeri MEOK North Bengkulu. This type of research is quantitative correlation. The sample in this study were 25 students. The instruments used are the step length measurement test and the 80 Meter short distance running test. The analysis used is Product Moment Correlation analysis with a significance level of 1%. Based on the results of the study, it shows that there is a significant relationship between step length and short distance running skills in fifth grade students of SD Negeri MEOK North Bengkulu, with a value of rx.y = 0.9454 > r (0.01) (25) = 0.505. There is a significant relationship between length (X) and 80 meter short distance running skills in fifth grade students of SD Negeri MEOK North Bengkulu.